Structural and optical properties of strontium titanate thin films prepared by spray pyrolysis - Mat, Siti Aisah (2014)
Strontium titanate (SrTiO3) thin films sample were prepared by using spray pyrolysis technique onto a glass substrate. The thin films were deposited using various concentrations of 0.2 – 1.0 M strontium nitrate (Sr(NO3)2) and titanium tetraisopropoxide (TTIP) at constant temperature 400ºC and a flow rate of 3 mL/min oxygen carrier gas. The films were annealed at temperature range of 400ºC to 650ºC. The films were characterized using UV-Visible spectrophotometer, X-ray diffractometer (XRD), atomic force microscope (AFM), Fourier transform infra-red spectrometer (FTIR) and photoluminescence (PL) spectrometer. The samples showed a high transmittance of more than 75% in the visible region, with band gap energy in the range of 3.4 eV to 4.0 eV. The band gap energy of the films decreased from 3.9 eV to 3.5 eV as the annealing temperature increased from 400ºC to 500ºC. The films deposited at 400ºC showed an amorphous phase. At an annealing temperature of 450ºC, the thin films sample turned into polycrystalline phase. The intensity of (110) orientation was the dominant phase of strontium titanate at annealing temperature of 650ºC. FTIR measurements showed that symmetrical OH absorption band exists in all the films and Ti-O bonding only can be observed at an annealing temperature 500ºC above. The grain sizes and surface roughness of the films increased with increasing annealing temperatures. In this study, the strontium titanate (SrTiO3) thin films did not show luminescent characteristic.